The actin released from profilin--actin complexes is insufficient to account for the increase in F-actin in chemoattractant-stimulated polymorphonuclear leukocytes (The Rockefeller University Press, 1990)
Chemoattractant stimulation of polymorphonuclear leukocytes is associated with a nearly two-fold rise in actin filament content. We examined the role of the actin monomer sequestering protein, profilin, in the regulation of PMN actin filament assembly during chemoattractant stimulation using a Triton extraction method. Poly-L-proline-conjugated Sepharose beads were used to assess the relative concentration of actin bound to profilin with high enough affinity to withstand dilution (profilin-actin complex) and DNase I-conjugated beads to measure the relative concentration of actin in the Triton-soluble fraction not bound to profilin. Actin associated with the Triton-insoluble fraction (F-actin) was also measured. In unstimulated PMN, the relative concentration of actin bound to profilin was maximum. After FMLP stimulation, profilin released actin monomers within 10 s, with the profilin-actin complex concentration reaching a nadir by 40 s and remaining low as long as the cells were exposed to chemoattractant (up to 30 min). If FMLP was dissociated from PMN membrane receptors using t- BOC, actin reassociated with profilin within 20 s. Quantitative analysis of these reactions, however, revealed that profilin release of and rebinding to actin could account for only a small percentage of the total change in F-actin content. Determination of the total profilin and actin concentrations in PMN revealed that the molar ratio of profilin to actin was 1 to 5.2. When purified actin was polymerized in PMN Triton extract containing EGTA, removal of profilin from the extract minimally affected (12% reduction) the high apparent critical concentration at which actin began to assemble. Although profilin released actin at the appropriate time to stimulate actin assembly during exposure to chemoattractants, the concentration of profilin in PMN was insufficient to explain the high unpolymerized actin content in unstimulated PMN and the quantity of actin released from profilin too small to account for the large shifts from unpolymerized to polymerized actin associated with maximal chemoattractant stimulation.